Correlation Between Traditional Law and Positivism in Indonesia and Malaysia - Iriansyah, Iriansyah; Irfansyah, Irfansyah; Febrina, Rezmia (Faculty of Law, Universitas Pekalongan, 2024)
This article aims to analyze the correlation between customary law and positivism law in Indonesia and Malaysia. This research uses a normative juridical approach with a statute approach and a conceptual approach. Based on the research results, customary law is unwritten with positivism law which is written. And positive law in Indonesia or the law that is expected to be present in the future in Indonesia, must be seen from the aspect of culture or customary law that grows and develops in the environment of indigenous peoples. Given the purpose of the form of a regulation or law is to meet human needs in social life. So the people who enjoy the law are the people. Whereas in Malaysia customary law is still recognized as long as it grows and develops in the community and does not conflict with the religion of Islam and has been promulgated, it can be said that there is the same thing as the distribution of assets gono gini or joint assets with Spencerian assets in Malaysia.